Clinical and Radiographical Evaluation Of Cariostatic Effect Of Silver Diamine Fluoride Individually And In Combination With Chemo-Mechanical Caries Removal Method: An In-Vivo Follow Up Study - Shaikh, Benzeer; Choudhari, Shantanu; Mittal, Swati; Vanza, Haresh; N, Rishitha; Gala, Miloni (Journal of Neonatal Surgery, 2025)
Early childhood caries remains a significant problem in pediatric population and to treat this young population with conventional drilling method is sometimes challenging. An In-vitro study by Hamama et al stated that Silver Diamine Fluoride following Chemo mechanical caries removal may have a synergistic antibacterial effect. So, the aim of present In-Vivo study was to evaluate clinically and radiographically cariostatic effect of Silver Diamine Fluoride individually and in combination with Chemo-mechanical Caries Removal (CMCR) method. A total 150 primary mandibular molars with proximal caries without pulpal involvement, in 3 to 6 years age group children were included and randomly and equally divided into 3 groups. In Group 1, caries was excavated with hand instrument and then restored with GIC. In Group 2, After caries removal using hand instrument, SDF was applied prior to restoration with GIC. In Group 3, Caries was removed with CMCR material then SDF was applied prior to restoration with GIC. Clinical and radiographical evaluation was done at 4, 8 and 12 months interval. At 12 months, clinical success of group 1 ,2 and 3 was 85.71%, 93.75% and 95.92% respectively and radiographic success was 85.71 %, 93.75% and 97.96%. There was difference in result between groups but no statistically significant difference found between Group 2 and Group 3 as p value was > 0.05. So, we can conclude that SDF alone and combination of CMCR and SDF has similar cariostatic effect but CMCR has added advantage of patient comfort and less anxiety.